Statistical properties of the surface velocity field in the northern Gulf of Mexico sampled by GLAD drifters. Issue 7 (30th July 2016) - Mariano, A. J.; Ryan, E. H.; Huntley, H. S.; Laurindo, L.C.; Coelho, E.; Griffa, A.; Özgökmen, T. M.; Berta, M.; Bogucki, D.; Chen, S. S.; Curcic, M.; Drouin, K.L.; et al.
Abstract: The Grand LAgrangian Deployment (GLAD) used multiscale sampling and GPS technology to observe time series of drifter positions with initial drifter separation of O(100 m) to O(10 km), and nominal 5 min sampling, during the summer and fall of 2012 in the northern Gulf of Mexico. Histograms of the velocity field and its statistical parameters are non‐Gaussian; most are multimodal. The dominant periods for the surface velocity field are 1–2 days due to inertial oscillations, tides, and the sea breeze; 5–6 days due to wind forcing and submesoscale eddies; 9–10 days and two weeks or longer periods due to wind forcing and mesoscale variability, including the period of eddy rotation. The temporal e ‐folding scales of a fitted drifter velocity autocorrelation function are bimodal with time scales, 0.25–0.50 days and 0.9–1.4 days, and are the same order as the temporal e ‐folding scales of observed winds from nearby moored National Data Buoy Center stations. The Lagrangian integral time scales increase from coastal values of 8 h to offshore values of approximately 2 days with peak values of 3–4 days. The velocity variance is large, O ( 1 )   m 2 / s 2, the surface velocity statistics are more anisotropic, and increased dispersion is observed at flow bifurcations. Horizontal diffusivity estimates are O ( 10 3 )   m 2 / s in coastal regions with weaker flow to O ( 10 5 )   m 2 / s in flow bifurcations, a strong jet, and during the passage of Hurricane Isaac. The Gulf of Mexico surface velocity statistics sampled by the GLAD drifters are a strong function of the feature sampled, topography, and wind forcing. Key Points: Velocity statistics are heterogenous, nonstationary, non‐Gaussian, and a strong function of feature sampled, topography, & wind forcing Large velocity variance, anisotropic velocity statistics, and horizontal diffusivity values of O(10 5 )m 2 /s are observed at bifurcations Fast transport pathways exist between the northern Gulf of Mexico and the southern Gulf of Mexico